On the Sound Shift Old Turkic /-d, -d-/ > /-z, -z-/ in Khwarezm Turkic Texts - Fatih Kurtulmuş (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Throughout history, Turks have experienced significant migration and conflict across a wide region of Asia and Eurasia. These movements have led to considerable political and cultural changes, which have, in turn, affected the linguistic structures and the relationships between dialects. In some instances, this has even resulted in the complete disappearance of certain dialects. With the arrival of various Turkic tribes, particularly the Oghuz and Kipchak, the Khwarezm region began to adopt Turkic characteristics. Subsequent waves of migration further mixed the Turkic population, creating a landscape where different Turkic dialects coexisted. This coexistence has resulted in a unique and, at times, complex linguistic structure. Over time, Khwarezm has become an important cultural center with a rich tradition of publishing works in Turkish. This article examines the status of the Old Turkic sound change /-d, -d-/ > /-z, -z-/ as observed during the Khwarezm Turkic period, particularly noted by Kashgarli Mahmud and prevalent in the Suvar, Yimek, and some Kipchak and Bulgarian tribes. We will analyze works from this period to discuss the reasons for this change, which appears in 25 words and 53 examples in the Anonymous Tafsir, and 24 words and 61 examples in certain copies of Kısasü’l-Enbiyâ. Additionally, we aim to uncover the contact between dialects and instances of archaism.